If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x+1)/6=2x-1
We move all terms to the left:
4(x+1)/6-(2x-1)=0
We get rid of parentheses
4(x+1)/6-2x+1=0
We multiply all the terms by the denominator
4(x+1)-2x*6+1*6=0
We add all the numbers together, and all the variables
4(x+1)-2x*6+6=0
We multiply parentheses
4x-2x*6+4+6=0
Wy multiply elements
4x-12x+4+6=0
We add all the numbers together, and all the variables
-8x+10=0
We move all terms containing x to the left, all other terms to the right
-8x=-10
x=-10/-8
x=1+1/4
| X+x+30=190 | | 25g-124=g | | 74-4p=18 | | x=4x-16/x^2+x+x-16/x^2+x | | 3a^2-5a-100=0 | | t=1779 | | 25x-124=x | | -7(5x-3)=-4(8x+6) | | 7p-3p-7p+5p=2p | | (X-964)x12=720 | | -.5(t+9)+5.75t=0.375t | | 4(2x-5)=2(7x+8) | | 4x-8=-4(2x3)+4 | | 2^x=74 | | 2/3x-78=6/72 | | 4a-2=5 | | 1.5/n=12/40 | | N2-n-56=0 | | 5/16=90/n | | 3x+2x=5x+3 | | (-17)+n/3=9 | | x2-21=100 | | 20x=4(2x-3) | | 19-3r=4 | | 41-2n=-10n-40 | | 7+2m-6=7m+28-2m | | x/4.2=10 | | x/42=0 | | y/42=10 | | 2(3x-10)=5(2x-8) | | 12m=364 | | 3r^2/3+2=50 |